Pengaruh Jumlah Uang Beredar, Ekspor, Impor dan Inflasi Terhadap Produk Domestik Bruto - Cahyani Islamiah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to determine the effect of money supply, exports, imports and inflation on gross domestic product. The research method uses quantitative with secondary data. Sampling used purposive sampling. The sample used in this research is Central Statistics Agency data, www.statistik.kemendag.go.id and www.bi.go.id for the 2012-2020 period, totaling 36 months. The analysis used is Multiple Linear Regression Analysis. This research was assisted by the SPSS 26 program. The results of the research showed that the T test with the money supply variable t was calculated at 3.543>1.69726 t table so that the money supply variable had a positive and significant influence on gross domestic product. The calculated export variable t is 3.729>1.69726 t table so that the export variable has a positive and significant influence on gross domestic product. The import variable t count is 1.414<1.69726 t table so that the import variable has a negative and insignificant influence on gross domestic product. The t calculated inflation variable is 41.407>1.69726 t table so that the inflation variable has a positive and significant influence on gross domestic product. The variables of money supply, exports, imports and inflation together have an influence on gross domestic product.